2012
DOI: 10.1093/jac/dks329
|View full text |Cite
|
Sign up to set email alerts
|

The newly described mecA homologue, mecALGA251, is present in methicillin-resistant Staphylococcus aureus isolates from a diverse range of host species

Abstract: Objectives: A previously unidentified mecA homologue, mecA LGA251 , has recently been described in methicillinresistant Staphylococcus aureus (MRSA) from humans and dairy cattle. The origin and epidemiology of this novel homologue are unclear. The objective of this study was to provide basic descriptive information of MRSA isolates harbouring mecA LGA251 from a range of host animal species.Methods: A number of S. aureus isolates from historical animal isolate collections were chosen for investigation based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
126
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(133 citation statements)
references
References 8 publications
3
126
1
3
Order By: Relevance
“…But in countries like Denmark, Netherland and Belgium, the report of MRSA CC398 in livestock is high (Köck et al, 2009a;Köck et al, 2009b). Epidemiological studies in UK indicate the spread of LA-MRSA into hospitals particularly in individuals with frequent animal contact (Paterson et al, 2012). Recently, there is evidence of MRSA transmission between human-to-animals and animals-to-humans (Umaru et al, 2011).…”
Section: Livestock-associated Mrsa (La-mrsa)mentioning
confidence: 99%
See 1 more Smart Citation
“…But in countries like Denmark, Netherland and Belgium, the report of MRSA CC398 in livestock is high (Köck et al, 2009a;Köck et al, 2009b). Epidemiological studies in UK indicate the spread of LA-MRSA into hospitals particularly in individuals with frequent animal contact (Paterson et al, 2012). Recently, there is evidence of MRSA transmission between human-to-animals and animals-to-humans (Umaru et al, 2011).…”
Section: Livestock-associated Mrsa (La-mrsa)mentioning
confidence: 99%
“…Lately, a new methicillin resistance mechanism gene, mecC was described in S. aureus (Porrero et al, 2014). García-Álvarez et al (2011), Paterson et al (2012), Walther et al (2012) and Paterson et al (2014) reported MRSA isolates carrying mecC gene from humans and animals. suggested the public health hazard of mecC-positive MRSA isolates as it has been isolated in human case and their livestock.…”
mentioning
confidence: 99%
“…is linked to the acquisition of mecA gene but a novel homolog, mecC located in a new staphylococcal cassette chromosome mec (SCCmec) cassette (SCCmec XI), has been identified and shown to have a 69% DNA sequence similar to mecA allotypes. 9 Isolates harboring mecC typically yield negative results for conventional mecA PCR, which can translate in detection errors in a subset of MRSA isolates 10 and subsequent therapeutic and public health implications.…”
Section: Introductionmentioning
confidence: 99%
“…12 Molecular characterization of isolates was performed by multilocus sequence typing (MLST), 13 SCCmec typing (type I-IV, XI), 10,14 and spa sequence typing. 15 The spa types were determined using the spaTyper software available at http://spatyper.fortinbras.us.…”
mentioning
confidence: 99%
“…As a result, the transpeptidase activity of PBP2a is functional at normally inhibitory concentrations of beta-lactam antibiotics, allowing cell wall synthesis to occur (2)(3)(4). Recently, a novel variant of mecA was identified in Staphylococcus aureus from cattle (5), humans, and a range of other animal species (6) in Denmark, France, The Netherlands, Ireland, Germany, Belgium, and the United Kingdom (5,(7)(8)(9)(10)(11). This subtype was originally designated mecA LGA251 but has since been renamed mecC and shares 70% nucleotide identity with the conventional mecA gene.…”
mentioning
confidence: 99%